2015
DOI: 10.1152/jn.00286.2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in visual and sensory-motor resting-state functional connectivity support motor learning by observing

Abstract: Motor learning occurs not only through direct first-hand experience but also through observation (Mattar AA, Gribble PL. Neuron 46: 153-160, 2005). When observing the actions of others, we activate many of the same brain regions involved in performing those actions ourselves (Malfait N, Valyear KF, Culham JC, Anton JL, Brown LE, Gribble PL. J Cogn Neurosci 22: 1493-1503, 2010). Links between neural systems for vision and action have been reported in neurophysiological (Strafella AP, Paus T. Neuroreport 11: 228… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…If motor learning by observing involves similar neural circuitry as active motor learning, we should also see somatosensory functional plasticity and behavioral changes with observation. While previous work has shown that observing FF learning involves concurrent changes in sensory-motor resting-state functional connectivity [7] and sensed limb position [8], these studies did not directly test the role of the somatosensory system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If motor learning by observing involves similar neural circuitry as active motor learning, we should also see somatosensory functional plasticity and behavioral changes with observation. While previous work has shown that observing FF learning involves concurrent changes in sensory-motor resting-state functional connectivity [7] and sensed limb position [8], these studies did not directly test the role of the somatosensory system.…”
Section: Discussionmentioning
confidence: 99%
“…The videos have been described in detail elsewhere [7]. Briefly, the videos showed a top-down view of a tutor performing the reaching task using the right arm.…”
Section: Methodsmentioning
confidence: 99%
“…Using this same dataset, we have previously examined changes in resting-state FC from pre-observation (day 1 scan) to post-observation (day 2 scan). See McGregor and Gribble (2015) for details of FC changes from day 1 to day 2, and how they relate to observation-related gains in motor learning.…”
Section: Experimental Designmentioning
confidence: 99%
“…Here we tested the hypothesis that individual differences in brain function or structure can predict the extent to which individuals will learn to perform a novel sensory-motor task (FF reaching) from observation. Based on our previous work (McGregor and Gribble, 2015;McGregor et al, 2016), we expected that individual differences in brain function and structure within visual and sensory-motor brain networks would be predictive of motor learning by observing. On day 1, subjects performed baseline (no FF) reaches using a robotic arm and then underwent preobservation anatomical and resting-state functional magnetic resonance imaging (fMRI) scans.…”
Section: Introductionmentioning
confidence: 99%
“…McGregor and Gribble, 2015). We assessed changes in resting-state functional connectivity 470 from pre-to post-observation that were related to behavioral measures of motor learning by 471 observing.…”
mentioning
confidence: 99%